Pembelajaran IPS Berorientasi Revolusi Industri 4.0 Melalui Infusing Blended Learning Di Sekolah Menegah Pertama - Sujarwo Sujarwo; Tubagus Ali Rachman (Institut Pendidikan Indonesia, 2022)
AbstractThe purpose of this research is to develop a learning model that is in accordance with the demands of the times in the industrial revolution era 4.0. Which has an impact on the shifting paradigm of learning patterns, namely learning patterns that use technology with learning that does not use technology, as well as the differences in learning concepts in class to be digital learning that doesn't have to be always in the classroom. This research uses the Research and Development approach by grouping it into three stages, namely: 1) Preliminary Study, 2) Program planning and preparation and 3) program trials. This research was conducted at 92 Jakarta Junior High School, in the even semester of the 2019/2020 Academic Year. The sampling technique in this study was a by purpose sampling by taking a sample of a group of students in class VII Junior High School 92 Jakarta. The results of this study develop a model of infusing blended learning carried out using cooperative and contextual learning models with a scientific approach and integrating or incorporating digital information technology into learning to use Google Classroom and kahoot! managed to improve student's learning outcomes and student's learning activeness. So, it can be concluded that the use of the blended learning model of learning by integrating Google Classroom and kahoot! in social studies learning is in accordance with the 4.0 industrial revolution which is characterized by the use of internet-based information technology and can be used as an alternative for teachers in learning innovation.Key Word: Industry Revolution 4.0, Infusing Blended Learning, Social Studies